Initial evidence-based analysis of risk levels per phases of flight, recency requirements and visual approach design in nighttime offshore helicopter operations - Nascimento, F.; Majumdar, A.; Ochieng, W.; Schuster, W. (My University, 2014)
The analysis of risks per phases of flight is fundamental for safe nighttime offshore helicopter operations. However, the poor quality of the safety data currently available limits the identification of critical issues on a per-phase-of-flight basis. To redress this problem, this paper develops a customised taxonomy of phases of nighttime offshore helicopter flights and uses it as the basis for a questionnaire survey on the phase-specific risk levels experienced by pilots. Additionally, the critical issues of flying recency requirements and visual approach design preferences are investigated. With the responses obtained from pilots located in seven countries, extensive statistical hypothesis testing shows that the phases involving visual scan techniques at high speed regimes are problematic, especially the visual segment of instrument approaches. Furthermore, the between-night-flights time gaps required for assured recency were found considerably shorter than currently standardised across the industry. A number of important implications result and should form the basis for future safety interventions